Kesia-siaan yang penuh makna: Kajian etis terhadap kata hebel dalam kitab Pengkhotbah - Nesimnasi, Ruben (KURIOS, 2024)
The Book of Ecclesiastes presents a skeptical and somber reflection on human existence. The term vanity serves as a central theme for Qohelet in expressing the outcomes of his existential inquiry. But what exactly does vanity mean in this context? This article examines the concept of futility from an ethical perspective, aiming to clarify common misunderstandings of the term. Uncertainties beyond our control mark human life; thus, vanity becomes a key concept for understanding how humans might transcend the world's absurdity. Ultimately, Ecclesiastes invites its readers to contemplate what it means to live rightly as creations of God. Abstrak manusia di dunia. Kesia-siaan menjadi kata kunci bagi Qõhelet dalam menyajikan hasil pergumulannya sebagai manusia. Lantas, apa yang dimaksud dari kesia-siaan? Artikel ini akan mendalami terminologi kesia-siaan dengan menggunakan lensa etis, untuk menghindari kekeliruan pemahaman tentang kesia-siaan. Manusia hidup di dalam ketidak-pastian yang berada di luar kontrol dirinya, sehingga kesia-siaan adalah kunci utama bagi manusia untuk melampaui ke-absurd-an duniawi. Kitab Pengkhotbah mendorong pembacanya untuk merenungkan kembali, bagaimana menjalani kehidupan yang sepantasnya sebagai ciptaan Allah.